2022
DOI: 10.1556/446.2022.00047
|View full text |Cite
|
Sign up to set email alerts
|

Changes in colour parameters and anthocyanin content of aseptically filled sour cherry juice during storage

Abstract: To overcome the problems of seasonality and geographical location in fruit production and processing, the production of aseptic semi-finished juice is an excellent solution. Even without refrigeration, aseptic pressing has a shelf life of more than a year, making it possible to produce finished products all year round. The production technology involves the addition of ascorbic acid to the pulp to fix or preserve colour. There is an increasing customer demand for ascorbic acid substitutes on the international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The antioxidant results obtained for control juice agree with the results of other researchers (Kahle et al, 2005;Ribárszki and Stéger-Máté, 2022). Results of EPA samples agree with the results measured in elderberry juice by Vujanović et al (2020).…”
Section: Resultssupporting
confidence: 90%
“…The antioxidant results obtained for control juice agree with the results of other researchers (Kahle et al, 2005;Ribárszki and Stéger-Máté, 2022). Results of EPA samples agree with the results measured in elderberry juice by Vujanović et al (2020).…”
Section: Resultssupporting
confidence: 90%
“…Depending on their pH, anthocyanidins can be reddish, pinkish, or orange (Piyapanrungrueang et al, 2016). Anthocyanidins are known for their health benefits as antioxidants and anti-inflammatories (Ribárszki et al, 2022;Joseph et al, 2014). Studies have shown that anthocyanins can reduce the occurrence of heart or blood vessel diseases, glucose-related issues, and cancer.…”
Section: Introductionmentioning
confidence: 99%